The influence of initial spinal cord haematoma and cord compression on neurological grade improvement in acute traumatic spinal cord injury: A prospective observational study - Sharwood, L.N.; King, V.; Ball, J.; Varma, D.; Stanford, R.W.; Middleton, J.W. (Journal of the neurological sciences, 2022)
Prospective observational cohort study linked with administrative data. Magnetic Resonance Imaging (MRI) is routinely performed after traumatic spinal cord injury (TSCI), facilitating early, accurate diagnosis to optimize clinical management. Prognosis from early MRI post-injury remains unclear, yet if available could guide early intervention. The aim of this study was to determine the association of spinal cord intramedullary haematoma and/or extent of cord compression evident on initial spine MRI with neurological grade change after TSCI. Individuals with acute TSCI ≥16 years of age; MRI review. Neurological gradings (American Spinal Injury Association Impairment Scale (AIS)) were compared with initial MRI findings. Various MRI parameters were evaluated for prediction of neurological improvement pre-discharge. 120 subjects; 79% male, mean (SD) age 51.0 (17.7) years. Motor vehicle crashes (42.5%) and falls (40.0%) were the most common injury mechanisms. Intramedullary spinal cord haematoma was identified by MRI in 40.0% of patients and was associated with more severe neurologic injury (58.3% initially AIS A). Generalised linear regression showed higher maximum spinal cord compression (MSCC) was associated with lower likelihood of neurological improvement from initial assessment to follow up prior to rehabilitation discharge. Combined thoracic level injury, intramedullary haematoma, and MSCC > 25% resulted in almost 90% probability of pre-discharge AIS (grade A) remaining unchanged from admission assessment. MRI is a vital tool for evaluating the severity and extent of TSCI, assisting in appropriate management decision-making early in TSCI patient care. This study adds to the body of knowledge assisting clinicians in prognostication. •Prospective multi-centre study, traumatic spinal cord injury including cervical and thoracic, n = 120.•Magnetic resonance imaging of all patients.•Various MRI parameters were evaluated for prediction of neurological improvement pre-discharge, including haematoma.•Thoracic injury, haematoma, and MSCC >25% gave ∼ 90% probability of AIS grade A at discharge – no change from admission.